Movement of nitrogen, phosphorus and potassium fertilizers in undisturbed soil columns as affected by soil compaction. - Sadegh-Zadeh, F.; A. W., Samsuri; Seh-Bardan, B. J (2008)
The objective of this study was to investigate the movement of the added fertilizers to soil as affected by soil compaction. In the experimented soil, three compaction levels were used. The soil was also irrigated for four times and after the each irrigation, Phosphorus (P) and Potassium (K) in the drainage water (effluent) was measured using standard methods. After the fourth irrigation, each soil column was divided to five equal parts and the elements in the columns were measured and finally the data were analyzed using the statistical software. The results showed that as the compaction is increased, the movement of nitrogen (N) and K downward is reduced, but the movement of P is increased. The reason for the movement of N in low compaction is the existence of macropores for preferential flow and suitable conditions for nitrification. The movement of the most of K in low compaction is due to movement through macropores and preferential flow. The increase in P movement in high compaction is caused by high moisture and movement by diffusion.